2014
DOI: 10.3762/bjoc.10.200
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of 1-alkoxy-1H-benzo- and 7-azabenzotriazoles from peptide coupling agents, mechanistic studies, and synthetic applications

Abstract: Summary(1H-Benzo[d][1,2,3]triazol-1-yloxy)tris(dimethylamino)phosphonium hexafluorophosphate (BOP), 1H-benzo[d][1,2,3]triazol-1-yl 4-methylbenzenesulfonate (Bt-OTs), and 3H-[1,2,3]triazolo[4,5-b]pyridine-3-yl 4-methylbenzenesulfonate (At-OTs) are classically utilized in peptide synthesis for amide-bond formation. However, a previously undescribed reaction of these compounds with alcohols in the presence of a base, leads to 1-alkoxy-1H-benzo- (Bt-OR) and 7-azabenzotriazoles (At-OR). Although BOP undergoes react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Although Cs 2 CO 3 was used previously, DBU was also effective and was used here, and good yields were obtained. In reactions with MeOH, allyl alcohol, and benzyl alcohol, 1-alkoxy-1 H -benzotriazoles 51 were observed to be byproducts (8–20%).…”
Section: Resultsmentioning
confidence: 99%
“…Although Cs 2 CO 3 was used previously, DBU was also effective and was used here, and good yields were obtained. In reactions with MeOH, allyl alcohol, and benzyl alcohol, 1-alkoxy-1 H -benzotriazoles 51 were observed to be byproducts (8–20%).…”
Section: Resultsmentioning
confidence: 99%
“…One is an attempted decarboxylative Heck reaction of the benzoate ester of HOBt with styrene, which gave a 25 % yield of 1,2 and 1,1 Heck arylation products . The other is a Pd‐mediated α‐allylation of ketones using the cinnamyl ether of BtOH (PhCH=CHCH 2 OBt) . The latter indicated the plausible formation of π‐allyl Pd complexes, which led us to consider Pd‐mediated C−C bond‐forming reactions of 1‐(aryl)methoxy‐1 H ‐benzotriazoles.…”
Section: Resultsmentioning
confidence: 99%
“…We have investigated benzotriazole‐based peptide coupling agents for nucleoside functionalization and other synthetic applications . In this context, we showed that 1‐alkoxy‐1 H ‐benzotriazoles (RCH(R′)OBt) are formed readily in reactions of alcohols with 1 H ‐benzotriazol‐1‐yl‐4‐methylbenzenesulfonate (BtOTs) and (1 H ‐benzotriazol‐1‐yloxy)tris(dimethylaminophosphonium) hexafluorophosphate (BOP) . Herein, we disclose the previously unknown reactivity of 1‐(aryl)methoxy‐1 H ‐ benzotriazoles in which a benzylic benzotriazolyloxy group acts as a nucleofuge in Pd‐mediated Csp3 −Csp2 cross‐couplings (Scheme ).…”
Section: Introductionmentioning
confidence: 90%
“…The reactions conducted via this approach were complete in shorter reaction times and produced higher yields as compared to the results of the two‐step, one‐pot approach. Only amines and thiols were tested, and because alcohols are known to react with BOP in the presence of base to produce the corresponding benzotriazol‐1‐yl ethers, they were not tested (Lakshman et al., ). This was further supported by observations that in the reaction with alcohols, small amounts of benzotriazol‐1‐yl ethers were isolated in the two‐step, one‐pot approach.…”
Section: Commentarymentioning
confidence: 99%
“…As in Basic Protocol 1, several alkyl and aryl amines and thiols were tested as nucleophiles in Basic Protocol 2. However, alcohols were not tested in this protocol, as they tend to react with BOP, and lead to the formation of corresponding benzotriazolyl ethers (Lakshman et al., ).…”
Section: Introductionmentioning
confidence: 99%